Assessment of the scientific debate on corruption and anti-corruption policy: a bibliometric approach - O.M. Lukashuk (Економіка, управління та адміністрування)
The article presents a bibliometric analysis of scientific publications on anti-corruption policy, focusing on the dynamics of academic interest, the geography of research, international scientific cooperation, and thematic clusters. The methodological basis of the study includes tools such as Google Trends, Bibliometrix, and VOSviewer, as well as data from the Scopus and Web of Science databases. The authors identify key trends in the search activity of Ukrainian users regarding corruption, analyze the leading countries in terms of publication output, the most cited sources, and the thematic content of scientific articles. Particular emphasis is placed on the relevance of studies devoted to transparency, accountability, judicial reform, institutional mechanisms, and the economic consequences of corruption. It is established that the highest research activity is demonstrated by authors from the United States, the United Kingdom, China, Ukraine, and several Eastern European countries. The analysis confirms the growing interdisciplinary approach to anti-corruption research, encompassing economics, law, political science, and sociology. The article contributes to the development of the scientific foundation for shaping effective state anti-corruption policies.